A family perspective on substance use disorder - Demircan, Dilara; Tamam, Lut (Journal of Dependence, 2024)
Substance use disorder is a disease with biological, psychological and social dimensions that deeply affects the family and is affected by the family. Many factors that cause substance use disorder have been identified in the literature. Family characteristics have an important place among these factors. In this review study, it was aimed to evaluate substance use disorder from a family perspective. Dysfunctional family characteristics are considered as a potential risk factor in the development of substance use disorder. At the same time, when family characteristics are qualified, they play a protective role. Genetic factors, having a family member with substance use disorder, family relationships and parenting styles constitute potential risky aspects of the family. Protective aspects can be considered as positive family relationships and functional parenting styles. After the development of substance use disorder, family participation in treatment is important. Regulation of dysfunctional relationships in the family, social support of the family and elimination of co-dependent behaviors are decisive in treatment. The fact that the prevention programs to be created cover the aspects of the family that may be risk factors and protective factors will increase the effectiveness of prevention programs. Treatment programs that include the family as well as the individuals diagnosed with substance use disorder and include the development of the family’s skills and support for the family will increase treatment motivation and prevent relapses.